Wood Density Variations of Tropical Trees Differing in Shade-Tolerance and Leaf Phenology of the Congo Basin (Global Journal of Science Frontier Research, 2023)
Abstract- Wood density WD is not only a key element in tropical forest ecology to estimate tree biomass but also an indicator of timber quality and it integrates many aspects of tree mechanical properties and functioning Notably contrasting patterns of radial variation of WD have been demonstrated and are related to regeneration guilds light- demanding vs shade-bearing but haven t been demonstrated to be related to leaf phenology deciduous vs evergreen With the destructive method and the archimed principle we investigated the WD radial variation of nine timber tree species harvested in the eastern region of Cameroon The result showed that WD differed significantly among these nine species P 0 05 Their average WD was 0 70 0 05 0 79 0 14 0 69 0 05 0 55 0 03 0 81 0 03 0 63 0 08 0 65 0 08 0 64 0 05 0 44 0 07 g cm3 for Afzelia bipendensis Cylicodiscus gabunensis Entandrophragma cylindricum Entandrophragma utile Erythrophleum suaveolens Mansonia altissima Milicia excelsa Pterocarpus soyauxii and Triplochiton scleroxylon Variation in WD from bark-to-pith enabled three distinct patterns type 1 in which WD increases A bipendensis type 2 in which WD decreases C gabunensis E cylindricum E utile E suaveolens M excelsa and P soyauxii and type 3 in which WD values are substantially equal M altissima and T scleroxylon All nine timber tree species were deciduous At the level of light requirement succession the pioneer species were E suaveolens M excelsa T scleroxylon and the other one was non-pioneer light demander species C gabunensis A bipendensis E cylindricum P soyauxii M altissima and E utile In addition we found that WD in this study compared to the DRYAD global repository may strongly differ depending on the species up to 133 for T scleroxylon and less than 96 for A bipendensis Therefore when estimating forest biomass in specific sites we recommend that future studies on WD include the analysis of the effect of vertical variation with long-term phenological data and anatomical analysis in the same species and use a large sampling size including individuals of both the same and different species
Keywords: wood density; radial variation; tropical forest; shade tolerance; leaf phenology; congo basin